Adsorption of Some Heavy Metal Ions onto Dernah’s Clay - El-Sarsour, Ibraheim A.; Kasem, Mohammad A.; Mansour, Saber E. (Al-Mukhtar Journal of Sciences, 2008)
Kaolinite clay is considered as a good adsorbent material since it is easily available at low cost and high capacity . Clay samples were taken from Dernah (Libya) and thermally treated in 200 and 500 ºC in addition to room temperature . Equilibrium isotherms have been determined for the adsorption of some heavy metal ions, namely, Cu2+, Ni2+ and Zn2+ from aqueous solutions onto clays treated at different temperatures . The obtained results show that the maximum adsorption capacity for Cu2+, Ni2+ and Zn2+, were 672, 620 and 589 ppm (for Clay-R), 672, 500 and 459 ppm (for Clay-200) and 427, 401 and 333 ppm (for Clay-500). Also, the untreated sample exposes higher adsorption than other calcined samples . Moreover, the order of the capacity is Cu2+> Ni2+ > Zn2+. The experimental results have been fitted with Langmuir and Frendlich isotherms . The Langmuir isotherm better fitted the experimental data since the average percent deviations were lower than with Frendlich isotherm .